Трехмерный МКЭ в расчетах колебаний вращающегося тела - Зайцев, Б. Ф.; Асаенок, А. В.; Ерецкая, Н. Е. (НТУ "ХПИ", 2008)
Побудовані рівняння коливань тіла, що обертається. Застосовано метод скінченних елементів в рухомій разом с тілом системі координат. Досліджено структуру матриць в рівняннях та окремі випадки виродження рівнянь.

The equations of vibrations of a rotating body are developed. The finite element method in the coordinate system which is moving together with a body is used. The matrix structures into the equations and particular cases of degeneracy of the equations are considered.
Keywords: НДС; ротор; конечный элемент; КЭ; матрица жесткости тела